Costly sexual dimorphism in Cyclommatus metallifer stag beetles. (12th June 2014) - Goyens, Jana; Dirckx, Joris; Aerts, Peter
Summary: In many animal species, male armature has evolved through sexual selection. This male weaponry can increase reproductive success, but only if the owner overcomes the associated costs. Male stag beetles bear one of the most extreme examples of male weaponry: their mandibles can be almost as long as their own body. We question whether the armature of male Cyclommatus metallifer negatively affects terrestrial locomotion (stability and cost). If so, we investigate whether these effects are potentially compensated by morphological and/or behavioural features, as seen in other specialized insect species. Conspecific females are used to represent the non‐dimorphed condition. The presence of the huge male mandibular apparatus shifts the body centre of mass (bCOM) anteriorly. Concomitantly, the male fore limbs are 28% longer and are systematically positioned in a more anterior angular sector than in females. Thus, the rostral border of the support area of the leg tripod also moves forward. This suggests a stability enhancing mechanism. However, in contrast to load‐carrying ants, the anteriorly placed bCOM still creates two pronounced statically instable periods each locomotor cycle. Due to the static instability, males must adjust their locomotor behaviour: they walk at higher cycle frequencies when compared to females of the same size, to ensure they proceed to the next stance before bumping to the ground with their heavy heads. Contrary to other specialized load‐carrying insect species, the (muscle) mass specific mechanical cost of transport of males exceeds that of females by 40%. Since neither stability nor cost of transport benefit from the male forelimb size and positioning, their role in guaranteeing adequate terrestrial locomotion while carrying an enlarged mandibular apparatus seems doubtful. Instead, the long limbs are themselves functional in fights, by pitching the body upwards in order to throw opponents backwards. The oversized male stag beetle armature comes at high ecological costs: locomotion economics as well as stability clearly suffer from the large mandibles. The observed limb length dimorphism does not prevent this, but should probably be considered part of sexual selection, rather than a compensation for its consequences. Abstract : Lay Summary Video